Effect of copper concentration on the properties of chemically deposited MoSb2-xCuxSe4/CdS thin film absorbing layer for photovoltaic applications. (January 2017) - Joy Jeba Vijila, J.; Mohanraj, K.; Sivakumar, G.
Graphical abstract: Highlights: Solar cell performance of Mo based materials are not explored elsewere. MoSb2-x Cux Se4 thin film was deposited by CBD method using EDTA as complexing agent. The films are stoichiometric and defect free. The higher carrier concentration (5.4044 × 10 20 ) and conductivity (0.009) of Cu 0.3M films leads to higher efficiency. By comparing the Mo based materials MoSb2-x Cux Se4 shows better PCE. Abstract: In this present work, a novel mixed metal chalcogenide MoSb2-x Cux Se4 nanocrystalline thin films deposited for different copper concentrations (x = 0.0 M, 0.1 M, 0.2 M & 0.3 M) on glass substrate using ethylenediaminetetraacetic acid (EDTA) as complexing agent by chemical bath deposition method at room temperature. XRD patterns revealed the incorporation of copper content by the conversion of orthorhombic Sb2 Se3 into Cu3 SbSe3 with a shift to higher angles. Average crystallite was found to be 134, 51, 34 and 17 nm for the deposited films. FTIR spectra confirm the presence of functional groups of Ethylenediaminetetraacetic acid (EDTA) and the metal oxide vibrations. FESEM analysis depicted the morphological changes with the addition of Cu content. UV–vis analysis shows higher absorption in the visible region and the band gap values are found to be 4.09–1.63 eV. Hall Effect analysis confirms the p-type nature of the material. The photo-current analysis shows higher photo-conversion efficiency of 1.78% for 0.3 M copper content.